The complete sequence of mitochondrial genome of Sinibotia pulchra (Cypriniformes: Cobitidae). (1st November 2016) - Yu, Peng; Yang, Qi-Chao; Ding, Shu-Quan; Zhang, Jun; Li, Xi-Lei; Bi, Zhi-Hua; Wan, Quan
Abstract: Sinibotia pulchra (Cypriniformes: Cobitidae) is a small cyprinid fish. In this study, the complete mitochondrial genome sequence of S. pulchra is sequenced. The S. pulchra complete mitochondrial genome (GenBank accession no. KT362179) was a circular molecule of 16 568 bp in length, with 13 protein-coding genes (PCGs), 2 ribosome RNA (rRNA) genes, 22 transfer RNA (tRNA) genes, an L-strand replication origin (OL) and a control region (D-loop). The nucleotide acid composition of the entire mitogenome was 31.69% for A, 25.63% for T, 26.94% for C and 15.74% for G, with an AT content of 57.32%. The AT content of 12S rRNA, 16S rRNA and D-loop was 50.21%, 56.86% and 66.74%, respectively.